Webit&NEU: An Embedded Device for the Internet of Things. (14th January 2014) - Wang, Jialiang; Zhao, Hai; Xu, Jiuqiang; Bi, Yuanguo
Abstract : The Internet of Things (IoT) is regarded as the future generation Internet, which ranges from radio frequency identification (RFID) to the ubiquitous computing systems such as wireless sensor networks and mobile ad hoc networks. With the rapid development of IoT, designing an effective low-cost embedded terminal device for the IoT become very necessary. A new embedded device, Webit&NEU, and its reduced embedded real-time operating system used for IoT are implemented by our China Liaoning Province Embedded Technique Key Laboratory in this paper. Besides, related modules in terms of RFID technique, wireless communication, and network protocol are also provided in this paper. Compared with several current solutions of connecting devices and Internet, it has the advantages of good real-time performance, light weight, and low cost. Besides, this paper also puts forward a localization algorithm for the Webit&NEU, and experimental test results in terms of real-time system ability, network communication performance, and localization algorithm show that Webit&NEU can work well and meet the actual requirements of the IoT.